2008
DOI: 10.1172/jci35147
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila are protected from Pseudomonas aeruginosa lethality by transgenic expression of paraoxonase-1

Abstract: Pseudomonas aeruginosa uses quorum sensing, an interbacterial communication system, to regulate gene expression. The signaling molecule N-3-oxododecanoyl homoserine lactone (3OC12-HSL) is thought to play a central role in quorum sensing. Since 3OC12-HSL can be degraded by paraoxonase (PON) family members, we hypothesized that PONs regulate P. aeruginosa virulence in vivo. We chose Drosophila melanogaster as our model organism because it has been shown to be a tractable model for investigating host-pathogen int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 62 publications
(80 reference statements)
4
72
0
Order By: Relevance
“…The ability of the PON enzymes to hydrolyse the HSL interrupts bacterial communication and reduces virulence. Whilst the intracellular PON2 variant shows the strongest lactonase activity, PON1is also active towards HSL (Ozer et al 2005) and is able to protect against Pseudomonas infection (Stoltz et al 2008). Indeed, PON1 is the major source of HSL neutralising activity in serum (Teiber et al 2008).…”
Section: Pon1 and Bacterial Pathogensmentioning
confidence: 99%
“…The ability of the PON enzymes to hydrolyse the HSL interrupts bacterial communication and reduces virulence. Whilst the intracellular PON2 variant shows the strongest lactonase activity, PON1is also active towards HSL (Ozer et al 2005) and is able to protect against Pseudomonas infection (Stoltz et al 2008). Indeed, PON1 is the major source of HSL neutralising activity in serum (Teiber et al 2008).…”
Section: Pon1 and Bacterial Pathogensmentioning
confidence: 99%
“…Like HDL ( 65,66 ), PON1 is an acute phase reactant and has been associated with the immune response ( 67,68 ) and infl ammation ( 69 ). Specifi cally, PON1 has been demonstrated to be a host modulator of Pseudomonas aeruginosa quorum sensing ( 35 ), with transgenic expression of PON1 being protective in Drosophila from infection lethality ( 36 ). Therefore, the fi nding of ITGAL SNP rs1557672 being associated with a decrease in PON1 activity ( ␤ coeffi cient = Ϫ 7.16) may indicate a further role of immune regulation of HDL, and specifically, PON1 activity.…”
Section: Description Of the Pon Gene Cluster Snvs In The Esp6500 Datamentioning
confidence: 99%
“…The lactonase activity of PON enzymes led to the hypothesis that they may also play a role in the attenuation of bacterial virulence by interfering with QS (Camps et al, 2011). In line with this hypothesis, it has been shown that overexpression of PON2 increases AHL inactivation in human airway epithelial cell lysates (Stoltz et al, 2008); additionally, of the three PON enzymes, PON2 exhibits the highest activity towards the important AHL, N-3-oxododecanoyl homoserine lactone (3OC12HSL). It has also been demonstrated that both PON1 and PON2 are important for the control of P. aeruginosa QS (Ozer et al, 2005;Teiber et al, 2008).…”
Section: Introductionmentioning
confidence: 74%